Methodological bases of game practice - Matsko, L. A.; Holovashenko, I. O. (Visnyk of Vinnytsia Politechnical Institute, 2013)
The phenomenon of game in contemporary humanities is analyzed, its ontological status and practical value is interpreted. Particular attention is drawn to the role of the game in psychology, and also its philosophical reflection. Content of the article demonstrates interdisciplinarity of game concept and trends of its research.